Pseudotachylyte-Mylonites Record of Transient Creep From Inter-Seismic Ductile to Co-Seismic Rupture - Dai, Wenhao; Zhou, Yongsheng; Ma, Xi (Frontiers in Earth Science, 2022)
Transient creep during an earthquake cycle is very important to understand the rheology of fault and deformation mechanisms in the brittle–plastic transition zone. In this paper, we analyzed the microstructures of samples for mylonites, pseudotachylyte, and cataclasite under optical microscope, SEM, and EBSD, which were collected from the Red River fault in southwest of China, where we uncovered a series of ductile to brittle deformed rocks which recorded transient creep related to earthquakes. The results show that mylonites formed at the inter-seismic creep were overprinted by pseudotachylyte and cataclasite which were produced during co-seismic rupture, and cracks in cataclasite were healed during the post-seismic relaxation. Based on the analysis of the microstructures and deformation mechanism of fault rocks, we propose the oscillation deformation model to explain transient creep of the brittle–plastic transition zone during the seismic cycle in the Red River fault.